2016
DOI: 10.1126/science.aae0065
|View full text |Cite
|
Sign up to set email alerts
|

The histone H3.3K36M mutation reprograms the epigenome of chondroblastomas

Abstract: Over 90% of chondroblastomas contain a heterozygous mutation replacing lysine 36 with methionine (K36M) in the histone H3 variant H3.3. Here, we show that H3K36 methylation is reduced globally in chondroblastomas and in chondrocytes harboring the same genetic mutation due to inhibition of at least two H3K36 methyltransferases, MMSET and SETD2, by the H3.3K36M mutant proteins. Genes with altered expression as well as H3K36 di- and trimethylation in H3.3K36M cells are enriched in cancer pathways. In addition, H3… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

16
228
4

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 229 publications
(261 citation statements)
references
References 49 publications
16
228
4
Order By: Relevance
“…To further determine the potency of the K36M as an inhibitor, we searched for the peptide signature of M36, based on its mass difference from K36, using mass spectrometry. Consistent with the low amount of K36M in tumors and cultured cells (Schwartzentruber et al, 2012;Behjati et al, 2013;Fang et al, 2016;Lu et al, 2016), we found that K36M peptides were present at an abundance of 1.4% among total detected H3.3 peptides (Supplemental Fig. S3A).…”
Section: K36m Mutation Exhibits a Dominant-negative Effect On Endogensupporting
confidence: 57%
See 3 more Smart Citations
“…To further determine the potency of the K36M as an inhibitor, we searched for the peptide signature of M36, based on its mass difference from K36, using mass spectrometry. Consistent with the low amount of K36M in tumors and cultured cells (Schwartzentruber et al, 2012;Behjati et al, 2013;Fang et al, 2016;Lu et al, 2016), we found that K36M peptides were present at an abundance of 1.4% among total detected H3.3 peptides (Supplemental Fig. S3A).…”
Section: K36m Mutation Exhibits a Dominant-negative Effect On Endogensupporting
confidence: 57%
“…Studies of K36M mutation in cell culture models suggest that endogenous H3K36 methylation reduction occurred through the inhibition of H3K36me3-specific Lys methyltransferases (Fang et al, 2016;Lu et al, 2016). Similarly, mutations of other histone Lys (K9 and K27) to Met also cause specific reduction in corresponding methylation levels by inhibiting SET-domain-containing methyltransferases (Lewis et al, 2013;Brown et al, 2014;Jayaram et al, 2016).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…All mice were maintained in a specific pathogen-free facility. SETD2-floxed mice were generated by Shangreported, SETD2 loss impairs ES cell differentiation (37) and expression of H3.3 mutants that inhibit H3K36 methylation compromises the differentiations of chondrocytes and mesenchymal progenitor cells (38,39). The Wnt pathway involves various feedback loops that balance the opposing processes of cell proliferation and differentiation.…”
Section: Methodsmentioning
confidence: 99%